Patient perceptions of tobacco control after smoke-free hospital grounds legislation: Multi-center cross-sectional study. (February 2020) - Martínez, Cristina; Castellano, Yolanda; Fu, Marcela; Riccobene, Anna; Feliu, Ariadna; Tigova, Olena; Ballbè, Montse; Anton, Laura; Fernández, Paz; Cabrera-Jaime, Sandra; Puig-Llobet, Montse; Moreno, Carmen; et al.
Abstract: Objective: To examine patient perceptions of the role of health care providers in tobacco control and tobacco-related services they should provide after the introduction of national smoke-free hospital grounds legislation in Spain. Design: Multi-center cross-sectional study. Setting: Thirteen hospitals in Barcelona province in 2014–2015. Participants: A total of 1, 047 adult hospital patients, with a stay ≥ 24 h were randomly selected. Method: We explored participants' perceptions of the role of health professionals and hospitals in tobacco control by asking about their agreement with several statements after the introduction of national legislation on smoke-free hospital grounds: (i) health professionals "should set an example and not smoke" and "should provide smoking cessation support"; (ii) hospitals "should provide smoking cessation treatments" and are "role model organizations in compliance with the smoke-free legislation", and (iii) "hospitalization is a perfect moment to quit smoking". Responses were described overall and according to participant and hospital characteristics: patient sex and age, type of hospital unit, number of beds, and smoking prevalence among hospital staff. Results: The majority of participants considered that health professionals should be role models in tobacco cessation (75.3%), should provide smoking cessation support to patients (83.0%), and that hospitalization is a good opportunity for initiating an attempt to quit (71.5%). Inpatients admitted to general hospitals where smoking cessation was not given as part of their portfolio, with a low level of implementation in tobacco control, and who stayed in surgical units had higher expectations of receiving smoking cessation interventions. Conclusions: Inpatients strongly support the role of hospitals and health professionals in tobacco control and expect to receive smoking cessation interventions during their hospital stay. Systematically providing smoking cessation services in hospitals may have a relevant impact on health outcomes among smokers and on health care system expenditures.